The TRIMS Agreement and its Implications on the Reality of Air Transport in Iraq - Nawzad Mahmoud Nadim*, Sozan; Mahmoud Rashid AlAni, Thaer (Journal of Economics and Administrative Sciences, 2024)
The research highlights the foreign direct investment environment in Iraq, and the importance of adopting the multilateral international agreement on trade-related investment measures (TRIMs), in light of Iraq’s accession to the world trade organization, in order to promote foreign direct investment. Investing in Iraq. Promoting an investment environment with international acceptance to attract foreign investments to Iraq, specifically in the Iraqi air transport sector, reviewing the most prominent challenges facing the investment environment in the Iraqi air transport sector, and obtaining the benefits and positives of these investments. The research aims to find an appropriate mechanism to achieve accession to the TRIMIS agreement and its implementation in the air transport sector, after overcoming the obstacles that appear before joining the world trade organization, in addition to clarifying the nature of the agreement with regard to investment procedures related to trade in goods and services. And reaching a future vision for foreign investment to develop the air transport services sector in Iraq. The results of the research showed that Iraq is capable of building a distinguished service sector, due to its financial and human capabilities, in order to improve the services of the Iraqi air transport sector, which leads to increasing the number of passengers, increasing flights, increasing the Iraqi air fleet and raising revenues, which contributes to increasing the added value. of the transportation sector in GDP.    Paper type: Research paper